High-resolution IP25-based reconstruction of sea-ice variability in the western North Pacific and Bering Sea during the past 18,000 years - Méheust, Marie; Stein, Ruediger; Fahl, Kirsten; Max, Lars; Riethdorf, Jan-Rainer (Geo-Marine Letters, 2016)
Due to its strong influence on heat and moisture exchange between the ocean and the atmosphere, sea ice is an essential component of the global climate system. In the context of its alarming decrease in terms of concentration, thickness and duration, understanding the processes controlling sea-ice variability and reconstructing paleo-sea-ice extent in polar regions have become of great interest for the scientific community. In this study, for the first time, IP25, a recently developed biomarker sea-ice proxy, was used for a high-resolution reconstruction of the sea-ice extent and its variability in the western North Pacific and western Bering Sea during the past 18,000 years. To identify mechanisms controlling the sea-ice variability, IP25 data were associated with published sea-surface temperature as well as diatom and biogenic opal data. The results indicate that a seasonal sea-ice cover existed during cold periods (Heinrich Stadial 1 and Younger Dryas), whereas during warmer intervals (Bolling-Allerod and Holocene) reduced sea ice or ice-free conditions prevailed in the study area. The variability in sea-ice extent seems to be linked to climate anomalies and sea-level changes controlling the oceanographic circulation between the subarctic Pacific and the Bering Sea, especially the Alaskan Stream injection though the Aleutian passes.